2020
DOI: 10.1111/acer.14427
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Genetic and Environmental Hedgehog Pathway Disruption Sensitizes Embryos to Alcohol‐Induced Craniofacial Defects

Abstract: Background: Prenatal alcohol exposure (PAE) is perhaps the most common environmental cause of human birth defects. These exposures cause a range of structural and neurological defects, including facial dysmorphologies, collectively known as fetal alcohol spectrum disorders (FASD). While PAE causes FASD, phenotypic outcomes vary widely. It is thought that multifactorial genetic and environmental interactions modify the effects of PAE. However, little is known of the nature of these modifiers. Disruption of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 100 publications
(125 reference statements)
0
21
0
Order By: Relevance
“…environmental risk factors further interacted with heterozygous mutation of shh (Everson et al, 2020). It should be emphasized that many potential environmental risk factors may require complementary insults for their effects to manifest [e.g., THC in 129S6 mice (Lo et al, 2021)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…environmental risk factors further interacted with heterozygous mutation of shh (Everson et al, 2020). It should be emphasized that many potential environmental risk factors may require complementary insults for their effects to manifest [e.g., THC in 129S6 mice (Lo et al, 2021)].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models will be helpful here. A recent study showed that PAE and PBO synergized in a zebrafish model of craniofacial defects, some of which resemble HPE; moreover, this combination of environmental risk factors further interacted with heterozygous mutation of shh ( Everson et al, 2020 ). It should be emphasized that many potential environmental risk factors may require complementary insults for their effects to manifest [e.g., THC in 129S6 mice ( Lo et al, 2021 )].…”
Section: Discussionmentioning
confidence: 99%
“…3 Notably, alcohol-induced craniofacial defects in zebrafish are increased by loss of a single allele of SHH or by exposure to piperonyl butoxide, another inhibitor of SHH signaling. 4 Several small molecules, including 17-β-estradiol and tolnaftate, have been identified as hedgehog signaling inhibitors with relevant human exposure. 35 Thus, a combination of Mkx mutation and environmental or genetic insults to SHH signaling may increase the risk of cleft palate.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research demonstrates that the Shh pathway is extremely sensitive to environmental attenuation. For instance, the common chemical synergist piperonyl butoxide (PBO) and many dietary molecules such as tomatidine and solanidine can inhibit Shh signaling [47][48][49]. Microsomia is thought to have a large environmental component [26].…”
Section: Implications For Variation In Human Birth Defectsmentioning
confidence: 99%